Open Ateliers 1994. (Antwerpen : Art Prom, 1994)
Baetens-Nolmans, Erik-Kris ; Ramael, Luc ; Donckers, Monique ; Casteleyns, Frank ; Philip, Stanley ; Van Bauwel, Wilfried ; Villas, Patrick ; Maur-Ice ; Van Woensel, Catherine ; Meukens, Tine ; Sluydts, Bruno ; De Koninck, Peter ; Boris ; Elsa V. ; Snyckers, Vera ; Van Der Meeren, Jacqueline ; Klagsbrun, Viviane ; Chapelle, Chantal ; Coen, Jean ; T'Seyen, Jos ; De Belder, Inge ; Pétré, Karla ; Vrijdaghs, Simonne ; Van Remoorter, Sibylle ; Baert, Lin ; Prinsen, Bart ; Verboven, Ann ; Boogerman, Rudolf ; Thomas, Eddy ; Bruynseels, Hilde ; Verheyen, Chris ; Tyukanov, Sergej ; Vuurstaek, Linda ; Den Haerynck, Jo ; Vets, Ludo ; Ysebaert, Thierry
Open Ateliers 1994, Stad Antwerpen, 17 & 18 en 24 & 25 september 1994
boek